1998
DOI: 10.1093/nar/26.16.3845
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and base-pairing studies of matched and mismatched DNA dodecamer duplexes containing cis-syn, (6-4) and Dewar photoproducts of TT

Abstract: Cis-syn dimers, (6-4) products and their Dewar valence isomers are the major photoproducts of DNA and have different mutagenic properties and rates of repair. To begin to understand the physical basis for these differences, the thermal stability and base pairing properties of the corresponding photoproducts of the TT site in d(GAGTATTATGAG) were investigated. The (6-4) and Dewar products destabilize the duplex form by approximately 6 kcal/mol of free energy at 37 degreesC relative to the parent, whereas a cis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 60 publications
4
76
0
Order By: Relevance
“…An NMR study of a duplex DNA with (6 -4)PP revealed that TT-(6 -4)PP greatly distorts the DNA structure and prevents base-pairing with A in the complementary strand (41). However, a mismatched base pair between the 3Ј-T of TT-(6 -4)PP and G forms hydrogen bonds and stabilizes the helix (42,43). Furthermore, the G/T mispair at the 3Ј-T of TT (6 -4)PP retains the normal WatsonCrick-type base-pairing between the 5Ј-T of the TT-(6 -4)PP and an opposed A, and the resultant GA/TT-(6 -4)PP duplex can assume the typical B-form-DNA conformation (44).…”
Section: Discussionmentioning
confidence: 99%
“…An NMR study of a duplex DNA with (6 -4)PP revealed that TT-(6 -4)PP greatly distorts the DNA structure and prevents base-pairing with A in the complementary strand (41). However, a mismatched base pair between the 3Ј-T of TT-(6 -4)PP and G forms hydrogen bonds and stabilizes the helix (42,43). Furthermore, the G/T mispair at the 3Ј-T of TT (6 -4)PP retains the normal WatsonCrick-type base-pairing between the 5Ј-T of the TT-(6 -4)PP and an opposed A, and the resultant GA/TT-(6 -4)PP duplex can assume the typical B-form-DNA conformation (44).…”
Section: Discussionmentioning
confidence: 99%
“…This discrimination function, presumably mediated by the presence of abnormal hydrophobic attractions on the helical surface and without specificity for a particular type of lesion, allows recognition of all damaged sites that destabilize (including for example cyclobutane pyrimidine dimers; ref. 39) or disrupt Watson-Crick hydrogen bonds. Therefore, XPA protein (together with RPA) may use this versatile strategy to target the human NER system to a wide range of chemically diverse forms of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Given that little difference has been observed in excision repair rates between inside and outside TT CPDs (41), the large difference in deamination rates could explain, at least in part, the origin of UV mutation hotspots and coldspots in phased nucleosomes that would arise following polymerase bypass. On the other hand, deamination of an m C-containing CPD will result in a T⅐G mismatch, which has been shown to destabilize the DNA duplex by 0.7 kcal/mol (54). This duplex destabilization may further destabilize the nucleosome, which has already been shown to be destabilized by 0.14 -0.24 kcal/mol by a TT CPD (41), and facilitate recognition by histone modification and/or excision repair systems.…”
Section: Figurementioning
confidence: 99%